Quimare Soluções LTDA: Report of the trails of an Interdisciplinary WebQuest - Nery Moncao , Nayana Bruna (2024)
This work presents data from the application of a WebQuest, which was based on the routine of a fictitious company - QUIMARE Soluções LTDA. Through it, high school students are encouraged to develop hygiene and personal care products. For this, an action containing eight attempts was organized, where each one of them requested the execution of a task and, in a collaborative way, organized tours to present the results according to what was requested. The data produced have a multimodal profile, for which several resources can be explored. In this process, the potential of using this methodology is reinforced, since, in this case, students can act as protagonists in the development of their knowledge in different areas of knowledge.